Cued Speech Gesture Recognition: A First Prototype Based on Early Reduction. (3rd January 2008) - Burger, Thomas; Caplier, Alice; Perret, Pascal
Abstract : Cued Speech is a specific linguistic code for hearing-impaired people. It is based on both lip reading and manual gestures. In the context of THIMP (Telephony for the Hearing-IMpaired Project), we work on automatic cued speech translation. In this paper, we only address the problem of automatic cued speech manual gesture recognition. Such a gesture recognition issue is really common from a theoretical point of view, but we approach it with respect to its particularities in order to derive an original method. This method is essentially built around a bioinspired method called early reduction . Prior to a complete analysis of each image of a sequence, the early reduction process automatically extracts a restricted number of key images which summarize the whole sequence. Only the key images are studied from a temporal point of view with lighter computation than the complete sequence.